Short term effects of anodal cerebellar vs. anodal cerebral transcranial direct current stimulation in stroke patients, a randomized control trial - Qurat-ul-ain,; Ahmad, Zafran; Ishtiaq, Summaiya; Ilyas, Saad; Shahid, Irum; Tariq, Iqbal; Malik, Arshad Nawaz; Liu, Tian; Wang, Jue (Frontiers in Neuroscience, 2022)
Background: Balance and gait impairments are major motor deficits in stroke patients that require intensive neuro-rehabilitation. Anodal transcranial direct current stimulation (tDCS) is a neuro-modulatory technique recently used in stroke patients for balance and gait improvement. Majority of studies focusing on tDCS have assessed its effects on cerebral motor cortex and more recently cerebellum as well but to our best knowledge the comparison of stimulating these two regions in stroke patients is not investigated so far. Objective: The current study aimed to compare the effect of anodal transcranial direct current stimulation on cerebellar and cerebral motor cortex M1 in stroke patients. Methods: This double-blinded, parallel, randomized, sham controlled trial included 66 patients with a first-ever ischemic stroke were recruited into three groups; Cerebellar stimulation group (CbSG), cerebral stimulation group (CSG) and Sham stimulation group (SSG). A total of three sessions of anodal transcranial direct current stimulation were given on consecutive days in addition to virtual reality based gait and balance training using Xbox 360 with kinect. The intensity anodal tDCS 2 mA applied for duration of 20 minutes. Results: The results of across group’s analysis showed a significant difference with p value < 0.05 for balance (BBS, TUG, BESTest), walking ability (6MWT, 25FWT), risk of fall (JHFRAT). However, cognitive function did not show any significant change among the groups with p value > 0.05. Multiple group analysis showed significant difference in both cerebellar and cerebral stimulation with p value < 0.05 for TUG, 25FWT, 6FWT, and JHFRAT where as cerebral stimulation showed significant improvement in comparison to sham stimulation for BBS (p = 0.008*) and BESTest (p = 0.027*). Conclusion: Findings of the study suggest Anodal tDCS stimulation of the cerebellum and cerebral motor cortex both improves gait, balance and risk of fall in stroke patients. However, both stimulation sites do not induce any notable improvement in cognitive function. Effects of both stimulation sites have similar effects in stroke patients.